An Epilogue. Social Network Analysis and Greco-Roman Politics - Ruffini, Giovanni R. (Journal of Historical Network Research, 2020)
A short synthesis of the chapters included in this volume with a critical reflection on the plus-value of social network analysis in ancient history.